2020
DOI: 10.3390/ijerph17124484
|View full text |Cite
|
Sign up to set email alerts
|

Environments, Behaviors, and Inequalities: Reflecting on the Impacts of the Influenza and Coronavirus Pandemics in the United States

Abstract: In the past century, dramatic shifts in demographics, globalization and urbanization have facilitated the rapid spread and transmission of infectious diseases across continents and countries. In a matter of weeks, the 2019 coronavirus pandemic devastated communities worldwide and reinforced the human perception of frailty and mortality. Even though the end of this pandemic story has yet to unfold, there is one parallel that is undeniable when a comparison is drawn between the 2019 coronavirus and the 1918 infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 62 publications
0
41
0
1
Order By: Relevance
“…Moreover, it has been found that over 30% of EWs would have to borrow money to pay for an unexpected US$500 medical bill (Kearney and Muñana, 2020). Compounding these economic circumstances, many Black Americans and other people of color have experienced challenges securing health-care access and insurance (Roberts and Tehrani, 2020). For instance, COVID-19 testing inequities have been observed throughout the pandemic (Tribune, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been found that over 30% of EWs would have to borrow money to pay for an unexpected US$500 medical bill (Kearney and Muñana, 2020). Compounding these economic circumstances, many Black Americans and other people of color have experienced challenges securing health-care access and insurance (Roberts and Tehrani, 2020). For instance, COVID-19 testing inequities have been observed throughout the pandemic (Tribune, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, people of color have been found to be overrepresented in many frontline industry occupations, such as bus drivers, postal workers, childcare workers, personal care aides, social workers, and nursing assistants, with approximately 41% identifying as Black, Hispanic, Asian American/Pacific Islander, or some classification other than White ( Rho et al, 2020 ). Likewise, many EWs have also been designated as economically vulnerable, as one in three reported living in a household earning less than US$40,000dollars a year, one in seven lacked health insurance, and millions have relied on government assistance programs ( Kearney and Muñana, 2020 ; Roberts and Tehrani, 2020 ). Based on data from the 2014–2018 American Community Survey, a substantial percentage of women, particularly women of color, have worked in low-wage jobs, including housekeeping cleaners (60%), nursing assistants (50%), and personal care aides (46%), which are jobs that can increase COVID-19 exposure because of the contact with coworkers and the public ( Frye, 2020 ; Roberts and Tehrani, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing urban open spaces often acted as open-air hospitals [6]. Exposure to fresh air, sunshine and gentle exercise were official treatment methods in the influenza pandemic [7] reducing the number of infections and deaths reported at open-air hospitals [8]. Medical research showed that regular meals, warmth, and plenty of fresh air and sunlight helped severely ill patients recover better than indoor nursed patients [8].…”
Section: Introduction 1health Benefits Of Green Infrastructure Durinmentioning
confidence: 99%
“…The relationship between TIG perception and social determinants of health (SDOH), or rather, factors that contribute to health, including the conditions of birth, growth, living, learning, working, playing and ageing, have been less understood. 71 Research has shown that the availability of affordable housing and increase of walkable streets, as well as a reduction in crime, are SDOH related to gentrification and, more specifically, TIG. 44 46 Although the presence of walkable streets during the construction period of TOD may be limited, the use of LRT after construction has been found to be associated with an increased likelihood of walking.…”
Section: Social Determinants Of Health Consequencesmentioning
confidence: 99%